Online social networking websites in innovation capability and hotels’ performance in Malaysia - Al-Shami, Samer Ali Hussein; Al Hammadi, Abdulla; Abdul Raheem, Hayder Adil; Al-Hammadi, Abdul Hadi; Abdul Rashid, Nurulizwa; Ali Alhammadi, Dheyab Eissa Badr (Emerald Group Publishing Ltd, 2021)
Purpose – The purpose of this study is to examine the role of social network websites (SNWs) on hotels’ performance through innovation, especially in emerging countries, which is still lacking. Design/methodology/approach – A survey was randomly distributed to 219 of 4- and 5-star hotels in Malaysia and the data were analyzed using the structural equation modeling. Findings – The results confirm that the SNWs have a positive effect on the innovation capacity; meanwhile, the innovation capacity fully mediated the association between online social networks and the firm’s performance. Moreover, the association between SNWs and innovation is partially mediated by absorptive capacity (AC). Originality/value – This paper deliberates the significance of online social networking websites in the improvement of innovation capabilities through business intelligence and information management that improve hotels’ performance. This paper also deliberates the methods in which online social networking websites improve AC and information management.